(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
An prominent Indian novelist, Kiran Desai, illustrates the influence that issues pertaining towomen’s education and child marriage have on the lives of her characters within the setting of moderndayIndian culture via the use of subjects that she deftly broaches in her books. Even though they are notthe primary emphasis, these themes provide depth to her stories and encourage readers to ponder theintricacies of gender roles, social expectations, and the transformational potential of education in the livesof women. Desai inspires critical introspection on these significant problems confronting contemporarysociety by way of her narratives.